ANALISIS PERILAKU ORGANIZATIONAL CITIZENSHIP BEHAVIOUR PADA KANTOR PUSAT PT. PERKEBUNAN NUSANTARA XI - Nadya Gea Elvira; Kustini Kustini (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study is useful in knowing the influence of Organizational Culture and Organizational Commitment on Organizational Citizenship Behavior (OCB) in employees. The population for this study is all workers of PT. Perkebunan Nusantara XI are 173 people with a total of 63 respondents. This study uses quantitative methods carried out at PT. Perkebunan Nusantara XI and used a technique for data collection by proportional random sampling. With the collection of data through observation, interviews and questionnaires. From the results of this study, it is found that if organizational culture has a positive and insignificant influence on OCB, it can be concluded that a high level of good organizational culture cannot increase the level of OCB. Organizational commitment has a positive and significant influence on OCB, it can be concluded that high organizational commitment can increase OCB well.